In-depth Review: Legal review on human rights enforcement in the ASEAN and EU context - Pratiwi, L. yes Esty; Saputro, Triyono Adi; Rahman , Kholilul; Arifin, Samsul; Islam, Muhammad Saiful (Journal of Law, Environmental and Justice, 2023)
ASEAN is one of the regional organizations without an inter-governmental regional human rights machinery. In addition, ASEAN must respond to the new phenomenon that human rights are no longer merely a problem within a country, but have become a problem between countries. On this basis the author carries out a legal comparison, because one of the points stated in the objectives in The ASEAN Charter, namely: respecting fundamental freedoms, promotion and protection of human rights, and promotion of social justice, as well as the establishment of an ASEAN human rights body, as a step to guarantee more concrete human rights certainty in ASEAN. The method used in this research is legal research with a common-core method approach which in general is the application of the functional method which is expanded by using the law in context method. The aim of this research is to unify the mechanisms for law enforcement and protection of human rights in ASEAN which are related to the authority of regional human rights institutions in deciding cases of violations of human rights so that they are in accordance with the objectives contained in the ASEAN Charter.